Green construction of eco-friendly phosphotungstic acid Sr-MOF catalysts for crystal violet removal and synthesis of coumarin and xanthene compounds. Issue 59 (19th November 2021) - Ibrahim, Amr A.; Ali, Shaimaa L.; Adly, Mina Shawky; El-Hakam, S. A.; Samra, S. E.; Ahmed, Awad I.
Abstract : There is an urgent need to improve engineering and synthetic chemistry, either through the use of eco-friendly starting materials or the proper design of novel synthesis routes. Abstract : There is an urgent need to improve engineering and synthetic chemistry, either through the use of eco-friendly starting materials or the proper design of novel synthesis routes. This reduces the contamination of toxic chemicals and helps the disposal of organic dyes. In the current work, a metal–organic framework-based Sr(ii ) was fabricated to achieve the desired goal for dye removal and catalysis. Sr-MOF-based phosphotungstic acid (PWA/Sr-MOF) was hydrothermally synthesized to study its adsorption and catalytic activities. Remarkably, about 99.9% of crystal violet (CV) dye was removed using PWA/Sr-MOF within 90 min at room temperature. Various factors have been studied to investigate the optimum conditions such as pH of solution, initial dye concentration, contact time, and temperature. The maximum adsorption capacity of CV dye was reached after 90 min and well fitted the pseudo-second kinetic order and Langmuir adsorption isotherm. Coumarin and xanthene reactions were chosen to test the catalytic activity of the prepared PWA/Sr-MOF at 373 K. Furthermore, structural and chemical characterization of the fabricated samples was obtained using FT-IR, XRD, TGA, DTA, TEM, EDX, and XPS. PWA/Sr-MOF can be considered as a promising and green framework in the material design used to study catalytic and adsorption performances.